Development of a system based on ArtificialIntelligence able to interact with suspects ofcybercrimes - Rocha Durán, Santiago; Ibañez Rodriguez, John David (Escuela Colombiana de Ingeniería Julio Garavito, 2020)
Este libro presenta el desarrollo del proyecto de grado “Development of a systembased on Artificial Intelligence able to interact withsuspects of cybercrimes”. El librocontiene el desarrollo de la teoría investigada y la implementación realizada durantela asignatura Proyecto de Grado. Se compone de la investigación, implementación ymejora del chatbot C3-Sex, enfocandose en los dos modelos utilizados para interactuarcon el sospechos (modelo basado en reglas y modelos retrieval), en la introducción deSnapchat como nueva plataforma para interactuar con el sospechos y en la mejora alclasificar el perfil del sospechoso. Estas mejoras permiten que la interacción con el sos-pechoso sea mucho mas eficaz permitiendo que el intercambio de contenido se de conmuchas más frecuencia y a su vez que los datos recolectados de cada conversación seananalizados de mejor manera

This book presents the development of the degree project “Development of a system based on Artificial Intelligence able to interact with suspects of cybercrime”. The book contains the development of the theory researched and the implementation carried out during the Degree Project. It is composed of the research, implementation and improvement of the C3-Sex chatbot, focusing on the two models used to interact with the suspect (rule-based model and retrieval model), on the introduction of Snapchat as a new platform to interact with the suspect and on the improvement of the suspect profile classification. These improvements make the interaction with the suspect much more effective by allowing the exchange of content to take place more frequently and the data collected from each conversation to be better analyzed.
Keywords: Chatbot; Pornografía infantil; Cibercrimen; Procesamiento natural; Lenguaje natural; Ciberseguridad; Chatbot; Child pornography; Cybercrime